Comparative analysis of antioxidant potential in leaf, stem, and root of Paederia foetida L. - Tasnima HUSNA; Mohammed MOHI-UD-DIN; Md. Mehedi HASAN; Anika NAZRAN; Haider Iqbal KHAN; Jahidul HASSAN; Md. Neamul Hasan SHOVON; Totan Kumar GHOSH (Acta Agriculturae Slovenica)
Paederia foetida L. is widely used for the treatment of myriad ailments. Thus, searching for plant parts having greater antioxidant potential would make it easy to get suitable materials for herbal drugs. The present effort was made to explore the antioxidant potentials in the plant parts of P. foetida grown under natural conditions by means of physiological and biochemical analyses. The young leaves showed the highest reservoir of non-enzymatic antioxidants such as chlorophylls (0.96 mg g-1), carotenoids (0.43 mg g-1), anthocyanins (53.99 µg g-1), phenolics (728.24 µg g-1), flavonoids (4178.05 µg g-1), and proline (1.46 µmol g-1) as compared to others. Total antioxidant activity was found to be the highest in young leaves (84.82 %) followed by young stems (80.24 %) and matured leaves (79.78 %). Analysis of enzymatic antioxidants resulted in the superior activity of ascorbate peroxidase (13.58 µmol min-1 mg-1) and glutathione S-transferase (3409 nmol min-1 mg-1) in young leaves whereas the highest rate of catalase (409.85 µmol min-1 mg-1) and peroxidase (3.5 nmol min-1 mg-1) activity were found in matured leaves. However, comparatively higher content of reactive oxygen species; hydrogen peroxide, and lipid peroxidation product; malondialdehyde in matured leaves than that of young leaves suggests that young leaf is a suitable source for herbal medicine.